Keanekaragaman Lichenes Di Kawasan Hutan Pinus Kragilan Kabupaten Magelang Provinsi Jawa Tengah - Anggraini, Listha Ivara, Efri Roziaty, S.Si M,Si (2017)
The Lichenes species found in the Kragilan Pine Forest of Magelang Regency Central Java Province has not been identified. The purpose of this research is to know the species and index of diversity Lichenes available in Kragilan Pine Forest of Magelang Regency Central Java Province. Data collection method used is survey method do at three research stations with different altitudes, which are 1300 mdpl, 1350 mdpl, and 1400 mdpl. Data of research result analyzed by descriptive quantitative presented in tables and figures. The results obtained 13 species of lichenes consists of 9 families which is dominated by Family Parmeliaceae. Researched on three station shows that the percentage of lichenes closure on the bark tree substrat showed different value. Each species in each station has a closing percentage value below 70%. Index of diversity (H`) that find in Kragilan Pine Forest included in the criteria H` < 1 that showed low diversity.